2020
DOI: 10.1161/circresaha.120.316743
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 9 Activates IKK to Regulate Atherosclerotic Plaque Vulnerability

Abstract: Rationale: Arterial inflammation manifested as atherosclerosis is the leading cause of mortality worldwide. Genome-wide association studies have identified a prominent role of histone deacetylase 9 (HDAC9) in atherosclerosis and its clinical complications including stroke and myocardial infarction. Objective: To determine the mechanisms linking HDAC9 to these vascular pathologies and explore its therapeutic potential for atheroprotection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 55 publications
5
58
0
Order By: Relevance
“…Consistently, HDAC9 deficiency in ApoE −/− mice resulted in evidently reduced lesion size in aortas and less advanced lesions (Azghandi et al, 2015). Further studies showed that HDAC9 could activate inhibitory κB kinase and regulate atherosclerotic plaque vulnerability (Asare et al, 2020). Moreover, HDAC9 repressed cholesterol efflux by downregulating ABCA1, ABCG1, and PPARγ and alternatively promoted macrophage activation in AS (Cao et al, 2014).…”
Section: Hdacs Regulate Atherosclerosis In Human and Animalsmentioning
confidence: 76%
“…Consistently, HDAC9 deficiency in ApoE −/− mice resulted in evidently reduced lesion size in aortas and less advanced lesions (Azghandi et al, 2015). Further studies showed that HDAC9 could activate inhibitory κB kinase and regulate atherosclerotic plaque vulnerability (Asare et al, 2020). Moreover, HDAC9 repressed cholesterol efflux by downregulating ABCA1, ABCG1, and PPARγ and alternatively promoted macrophage activation in AS (Cao et al, 2014).…”
Section: Hdacs Regulate Atherosclerosis In Human and Animalsmentioning
confidence: 76%
“…Furthermore, Hdac9 −/− LDLr −/− BMMs have increased expression of M2 markers and decreased expression of M1 inflammatory genes, resulting in macrophage polarization towards an M2‐like phenotype via increased total H3Ac, H4Ac and H3K9Ac at the promoters of Pparg and up‐regulated expression of Pparg 59 . Hdac9 –/– Apoe –/– BMMs have reduced TNF‐α‐induced up‐regulation of pro‐inflammatory gene expression, and during the development of atherosclerosis, HDAC9 binds to, deacetylates and activates inhibitory kappa B kinase (IKK)‐α and β, driving inflammatory responses in macrophages and endothelial cells 53 . Interestingly, DNA methyltransferase Dnmt3a up‐regulates the expression of Hdac9, to deacetylate the key PRR signalling molecule TBK1 and to activate the transcription of type I interferon genes in primary PM during innate antiviral immunity 60 .…”
Section: Discussionmentioning
confidence: 99%
“… 17 In contrast, Hdac6 KO BMMs show normal LPS‐induced expression of inflammatory genes endothelin‐1 ( Edn‐1 ) and IL12p40 . 52 Notably, Class IIa HDAC inhibitors attenuate inflammation in mouse and human macrophages, 49 , 53 stabilize atherosclerotic plaques in mice and limit the expression of inflammatory factors IL‐1β and IL‐6 in monocytes from patients with atherosclerosis, a chronic arterial inflammatory condition. 53 Therefore, it is reasonable to consider that high‐level expression of HDAC9, a class IIa HDAC member, in M2 is involved in suppressing key genes that drive M2 differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelium plays a pivotal role in the progression of AS and its complications, and endothelial dysfunction is widely recognized as one of the early alterations in the vessel wall preceding the development of plaques [24,25]. Emerging evidence has shown that the degree of endothelial cell (EC) apoptosis may be a key factor in the transition of a plaque from a stable state to a fragile state [26,27].…”
Section: Endothelial Cellsmentioning
confidence: 99%